Strategy to Handling The Challenges of Small-Scale Fisheries Vulnerability - Fitriyah, Silviaanis; Susilowati, Indah; Kusumawardhani, Hapsari Ayu (Eko-Regional: Jurnal Pembangunan Ekonomi Wilayah, 2024)
This study aims to identify the vulnerability of small-scale fishermen in the Roban Coastal Area through fast variables and slow variables, identify the adaptive capacity of fishermen to social-ecological changes, and analyze the resilience strategy of fishermen in facing rapid social-ecological changes due to national strategy projects. The method used was a mixed method with descriptive statistical analysis and 100 small-scale fishermen were taken as samples through purposive sampling. The results obtained show that the level of vulnerability of small-scale fishermen is in the high vulnerability category with a score of 7.89, the most vulnerable indicator is dependence on nature. The Roban Coastal small-scale fishermen resilience strategy is carried out through interdependence between stakeholders (academics, business people, government, and community) by obtaining the results that need to pay attention to several aspects (social, environmental, economic) in facing changes so that fishermen have a resilient level of resilience.